Usulan Perbaikan Kualitas Produk Tas Wanita dengan Metode Statistical Quality Control (SQC) dan Failure Mode and Effect Analysis (FMEA) - Farhan Fahmi; Iyan Bachtiar; Dewi Shofi Mulyati (UNISBA Press, 2024)
Abstract. Kharisma Leather Home Industry is a fashion industry in the field of leather crafts. The company experienced a decrease in turnover due to defective products produced during the production process. The defective products produced include sling bags and handbags with defect rates of 5.58% and 9.05% respectively. The types of defects that often occur are less precise stitching, defective materials, and damaged inner lining. This research aims to provide suggestions for improving the quality of women's leather bags.Data collection is done through observation and interviews. The methods used in this research are Statistical Quality Control (SQC) and Failure Mode and Effect Analysis (FMEA). The data needed to design the proposed improvements are data on the number of products produced and the number of defective products per month in 2022. The data is used to be described with a histogram diagram and then processed to determine the control limits on the p control map and then sorted using a Pareto diagram and identified the cause of the defect with a cause-and-effect diagram and then the calculation of the Risk Priorty Number (RPN) is carried out to provide proposed improvements. The results of this study show that the main priority for improvement lies in the defect of imprecise stitching caused by inconsistent material thickness and lack of focus of workers with an RPN value of 120. The repair of defective materials is done by correcting errors in the selection of materials with an RPN value of 120. The damaged inner layer is caused by the lack of skill of workers and materials that are easily torn with an RPN value of 72. The proposed improvements include operator training, stricter supervision, setting production schedules, and making and implementing more effective SOPs. Abstrak. Home Industry Kharisma Leather merupakan industri fashion di bidang kerajinan kulit. Perusahaan mengalami penurunan omzet akibat produk cacat yang dihasilkan selama proses produksi. Produk cacat yang dihasilkan meliputi tas selempang dan tas tangan dengan tingkat kecacatan masing-masing sebesar 5,58% dan 9,05%. Jenis cacat yang sering terjadi adalah jahitan kurang presisi, bahan cacat, dan lapisan dalam yang rusak. Penelitian ini bertujuan untuk memberikan usulan perbaikan kualitas tas kulit wanita. Pengumpulan data dilakukan melalui observasi dan wawancara. Metode yang digunakan pada penelitian ini yaitu Statistical Quality Control (SQC) dan Failure Mode and Effect Analysis (FMEA). Data yang dibutuhkan untuk perancangan usulan perbaikan yaitu data jumlah produk yang diproduksi dan jumlah produk cacat tiap bulan pada tahun 2022. Data tersebut digunakan untuk digambarkan dengan diagram histogram kemudian diolah untuk menentukan batas kendali pada peta kendali p kemudian diurutkan menggunakan diagram Pareto dan diidentifikasi penyebab kecacatan dengan diagram sebab-akibat kemudian dilakukan perhitungan Risk Priorty Number (RPN) untuk diberikan usulan perbaikan. Hasil penelitian ini menunjukkan bahwa prioritas utama perbaikan terletak pada cacat jahitan tidak presisi yang disebabkan oleh ketidakkonsistenan ketebalan bahan dan kurang fokusnya pekerja dengan nilai RPN 120. Perbaikan bahan cacat dilakukan dengan memperbaiki kesalahan dalam pemilihan bahan dengan nilai RPN 120. Lapisan dalam yang rusak disebabkan oleh kurang terampilnya pekerja dan bahan yang mudah sobek dengan nilai RPN 72. Usulan perbaikan yang diberikan meliputi pelatihan operator, pengawasan yang lebih ketat, pengaturan jadwal produksi, serta pembuatan dan implementasi SOP yang lebih efektif.